Finite Element Thermal Simulations for the Design of Mold Conformal Heating Channels Manufactured by 3D Printing Sand Casting for Molding of EPDM Rubber - Abbès, Boussad; Abbès, Fazilay; Upganlawar, Aditya (Journal of Modern Mechanical Engineering and Technology, 2018)
This paper presents an application of Additive Manufacturing (AM) technology that is suitable for manufacturing molding tools with conformal heating channels to increase productivity for EPDM rubber molding. The design and the manufacturing of a molding tool by combining 3D sand printing and casting processes was analyzed. A simplified finite element thermal analysis was used to optimize the EPDM molding cycle time of an automotive hood seal. The simulation results showed that by using a mold with conformal heating channels manufactured by 3D printing sand casting, the cycle time process of EPDM can be reduced by 41.5%.